2016
DOI: 10.1002/ls.1343
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of borate ester and evaluation of its tribological properties as an additive in different base oils

Abstract: N‐containing borate ester (MEBE) with five‐member ring structure as a lubricant additive was synthesised. The tribological properties in liquid paraffin (LP), poly‐alpha‐olefin (PAO) and dioctyl sebacate (DOS) were evaluated, and the action mechanisms in different base oils were also explored. It was found that as‐synthesised borate ester possesses excellent antiwear performance in LP and PAO. XPS analysis suggests that the additive forms a protective film on the rubbing surfaces which is composed of BN, Fe2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…However, the WSD increases with further increase of additive concentration above 1.0%. Furthermore, compared with MEBE borate synthesized in the past, 25 the antiwear property of DEBE was superior to that of MEME at low additive concentration (less than 0.6% in LP). However, when the additive concentration was more than 0.6%, DEBE is lower in antiwear performance than MEBE.…”
Section: Characterization Of As-synthesized Borate Estermentioning
confidence: 86%
See 3 more Smart Citations
“…However, the WSD increases with further increase of additive concentration above 1.0%. Furthermore, compared with MEBE borate synthesized in the past, 25 the antiwear property of DEBE was superior to that of MEME at low additive concentration (less than 0.6% in LP). However, when the additive concentration was more than 0.6%, DEBE is lower in antiwear performance than MEBE.…”
Section: Characterization Of As-synthesized Borate Estermentioning
confidence: 86%
“…4 depicts the relationship between friction coefficient and additive concentration in LP, PAO and DIOS base oils under the applied load of 200 N (corresponding to the maximum Hertz Contact Pressure is 2664 MPa). 25 It can be seen from the curves that the friction coefficient decreased slightly when DEBE borate ester was introduced into DIOS. And the friction coefficient sometimes was even a little higher than the one under the lubrication of LP alone, as the additive concentration in LP increased, Furthermore, under the same conditions, the friction coefficient of DEBE in liquid paraffin is lower than that of MEBE borate ester in liquid paraffin which is we synthesized in the past.…”
Section: Characterization Of As-synthesized Borate Estermentioning
confidence: 97%
See 2 more Smart Citations
“…In the carbon spectrum, the C1s peaks located at 283.72 eV and 284.75 eV were the main components and were attributed to C-C and C-O bonds of organic compounds, which suggested that the decomposition products of the base oil were adsorbed on the worn surface. 33 Another peak at 286.35 eV was assigned to the COO functional group from the additional surfactants. Moreover, environmental contamination during the sliding test or the addition of an impurity during the wireelectrode cutting process may have contributed to this peak.…”
Section: Xps Analysismentioning
confidence: 99%